Gastric Bypass Resolves Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD) in Low-BMI Patients: A Prospective Cohort Study. Issue 5 (26th November 2022) - Billeter, Adrian T.; Scheurlen, Katharina M.; Israel, Barbara; Straub, Beate K.; Schirmacher, Peter; Kopf, Stefan; Nawroth, Peter P.; Müller-Stich, Beat P.
Abstract : Objective: Metabolic dysfunction-associated fatty liver disease (MAFLD) reflects the multifactorial pathogenesis of fatty liver disease in metabolically sick patients. The effects of metabolic surgery on MAFLD have not been investigated. This study assesses the impact of Roux-en-Y gastric bypass (RYGB) on MAFLD in a prototypical cohort outside the guidelines for obesity surgery. Methods: Twenty patients were enrolled in this prospective, single-arm trial investigating the effects of RYGB on advanced metabolic disease (DRKS00004605). Inclusion criteria were an insulin-dependent type 2 diabetes, body mass index of 25 to 35 kg/m 2, glucagon-stimulated C-peptide of >1.5 ng/mL, glycated hemoglobin >7%, and age 18 to 70 years. A RYGB with intraoperative liver biopsies and follow-up liver biopsies 3 years later was performed. Steatohepatitis was assessed by expert liver pathologists. Data were analyzed using the Wilcoxon rank sum test and a P value <0.05 was defined as significant. Results: MAFLD completely resolved in all patients 3 years after RYGB while fibrosis improved as well. Fifty-five percent were off insulin therapy with a significant reduction in glycated hemoglobin (8.45±0.27% to 7.09±0.26%, P =0.0014). RYGB reduced systemic and hepatic nitrotyrosine levels likely through upregulation of NRF1 and its dependent antioxidative and mitochondrial genes. In addition, central metabolic regulators such as SIRT1 and FOXO1 were upregulated while de novo lipogenesis was reduced and β-oxidation was improved in line with an improvement of insulin resistance. Lastly, gastrointestinal hormones and adipokines secretion were changed favorably. Conclusions: RYGB is a promising therapy for MAFLD even in low-body mass index patients with insulin-treated type 2 diabetes with complete histologic resolution. RYGB restores the oxidative balance, adipose tissue function, and gastrointestinal hormones.